HUBUNGAN ANTARA TINGKAT STRES DENGAN KEJADIAN DISMENOREA PADA REMAJA PUTRI KELAS XII DI SMA NEGERI 1 KUNINGAN - Nurdewi Sulymbona; Abdal Rohim; Andra Mories K (Journal Of Midwifery And Nursing Studies, 2023)
Background: Severe pain or pain, which we call dysmenorrhoea, occurs in the lower part of the abdomen when women experience the menstrual cycle. The pain usually lasts just before menstruation, during menstruation, until the end of menstruation. One of the factors that causes dysmenorrhea in teenagers is stress, stress can disrupt the endocrine system so that it can cause irregular menstruation and pain during menstruation or dysmenorrhea. In West Java, it is estimated that 30% -70% experience menstrual problems, including stomach pain or stomach cramps. As many as 7 out of 10 teenage girls in class XII at SMA Negeri 1 Kuningan experience pain when menstruating. Objective: to determine the relationship between stress levels and the incidence of dysmenorrhea in class XII teenage girls at SMA Negeri 1 Kuningan. Method: quantitative research with a descriptive analytical approach. The population and sample in this study were all teenage girls in class XII at SMA Negeri 1 Kuningan, totaling 70 respondents using a random technique. The instruments used were the DASS questionnaire and the NRS scale. Data analysis was carried out using Spearman Rank. The data source used is primary data. Results: Bivariate analysis of the 2 variables studied resulted in ?-value = 0.001 with the strength of the relationship in the weak category in a positive direction (R = 0.377). Conclusion: There is a relationship between stress levels and the incidence of dysmenorrhea in class XII teenage girls at SMA Negeri 1 Kuningan. There is a need for good coping mechanisms in dealing with various problems and a healthy lifestyle is needed so that stress can be reduced so that young women do not experience dysmenorrhea. Keywords : Stress level1, incidence of dysmenorrhea2, Teenage girl3